Von Willebrand Factor Multimer Patterns in Pregnancy-Induced Hypertension - Brenner, B; Zwang, E; Bronshtein, M; Seligsohn, U (Thrombosis and Haemostasis, 1989)
Microangiopathy and disseminated platelet aggregation have been reported in thrombotic thrombocytopenic purpura (TIP) and pregnancy-induced hypertension (PIH). Since unusually large von Willebrand factor (vWF) multimers have been implicated in the evolvement of TTP, we analyzed factor VIII/vWF parameters in patients with PIH. Mean vWF: Ag level was significantly higher in 27 patients with PIH as compared to 20 matched healthy pregnant women (358 ± 160 u/dl vs. 274 ± 125 u/dl, p < 0.05). Moreover, plasma vWF: Ag levels and the ratio of vWF: Ag to factor VIII were found to be linearly correlated to the severity of PIH. In contrast, no significant differences in mean levels of factor VIII and ristocetin cofactor were observed between these groups. Crossed immunoelectrophoresis of vWF revealed a higher incidence of a pre-peak and an increased migration index in the PIH group as compared to the control group (60% vs. 44% and 1.27 ± 0.26 vs. 1.19 ± 0.18, p < 0.01 respectively). Analysis of plasma vWF multimer patterns by 1.4% agarose electrophoresis in 0.1% SDS revealed excessive amounts of large, medium and small size multimers in the PIH patients. Conceivably, the quantitative changes in vWF multimers reflect endothelial injury and may play a role in the microangiopathy observed in PIH.
Keywords: Pregnancy-induced hypertension; Factor VIII; von Willebrand factor; Fetal growth retardation